Managerial Dynamic Capabilities And Small And Medium-Sized Enterprises’ Internationalization: Moderating Role Of Environmental Dynamism - Valiappan Raju, Hussein Taleb (International Journal of Advanced Science and Technology, 2020)
Despite the internationalization literature has presented various approaches to internationalization, there is a lack of consensus and evidence on how owners/managers of SMEs reach and compete in international markets. This paper contributes to this issue through investigating the role of dynamic capabilities possessed by owners/managers namely, sensing, seizing and reconfiguring capabilities in enhancing the internationalization of SMEs. In addition, this study argues that environmental dynamism has moderating effects on the relationship between dynamic capabilities and SMEs internationalization. The data collection for this research employed a survey questionnaire to collect primary data from 300 owners/managers of internationalized Malaysian manufacturing SMEs in Malaysia. The research findings have revealed a significant relationship between dynamic capabilities and SME internationalization as well as a significant moderating effect of environmental dynamism on this relationship. A set of recommendations and further research put an end to this paper.